2006
DOI: 10.1007/s10339-006-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

A framework for assessing the salience of landmarks for wayfinding tasks

Abstract: Background Landmarks play an important role for the understanding of and reasoning about physical large-scale space. Landmarks also play an important role in every day's spatial tasks, such as wayfinding and navigation. The property of being a landmark has so far been attributed to distinct objects, which are either well known or otherwise unique, such as the Eiffel Tower or a lighthouse on the shore. We propose a framework for the assessment of the landmarkedness of potential landmarks for wayfinding tasks, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Third, in our experiment, participants had to perform a distracter task when they explored the virtual landmarks and corridors that they had to remember. This distracter task was primarily used because it was shown that multisensory memory effects were larger when such a task was employed [19]. When navigating the real world the benefits of multisensory presentation would be lower if such distracter tasks do not exist.…”
Section: How Representative Is Our Setup For Real World Situations?mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, in our experiment, participants had to perform a distracter task when they explored the virtual landmarks and corridors that they had to remember. This distracter task was primarily used because it was shown that multisensory memory effects were larger when such a task was employed [19]. When navigating the real world the benefits of multisensory presentation would be lower if such distracter tasks do not exist.…”
Section: How Representative Is Our Setup For Real World Situations?mentioning
confidence: 99%
“…Landmarks are typically distinctive objects that stand out in the environment [18,19] and serve as reference points when we are following routes or when we need to determine where we are [4]. When navigating the real world, landmarks can be seen (e.g.…”
Section: Multisensory Perception Of Landmarksmentioning
confidence: 99%
“…In sighted people, visual cues such as landmarks (Golledge, 1999) are important for all aspects of environmental learning and navigation (Caduff & Timpf, 2007). Tom and Denis (2004), for example, showed that individuals learn and remember landmarks easier than street names when learning a new route, possibly due to the visual image that landmarks facilitate.…”
Section: Environmental Influences On Encoding Cognitive Mapsmentioning
confidence: 99%
“…These studies and others (Evans, Brennan, Skorpanich, & Held, 1984;Goodman, Brewster, & Gray, 2005) indicate that older adults have more difficulty learning new environments and may be more dependent on salient environmental cues than younger adults. Caduff and Timpf (2007) also suggested that cues must be salient to be most effectively used for wayfinding and navigation. They further propose that overall salience is determined by three subsets of salience: perceptual, cognitive, and contextual.…”
Section: Environmental Influences On Encoding Cognitive Mapsmentioning
confidence: 99%
See 1 more Smart Citation